International determinants of comprehensive income reporting by groups: An analytical and comparative study of Poland and Germany - Jakub Kwaśny; Artur Sajnóg (Comparative Economic Research. Central and Eastern Europe, 2022)
The mainstream theoretical and empirical research presented in the study is a comparative analysis of comprehensive income reporting by groups listed in the Polish and German capital markets. The theoretical part of the article is dedicated to a scientific discussion on the determinants of the capital market and corporate governance in continental Europe and the so-called 'new governance', related to the convergence of financial reporting standards, including IFRSs, that oblige groups of entities to prepare consolidated statements of comprehensive income. It also assesses the relevance of comprehensive income to capital market players. The empirical part contains the results of comparative research on the format and structure of consolidated statements and the nomenclature of their components, as well as the findings from studies of the value relevance of comprehensive income for the WIG30 and DAX groups in 2009-2019.
Keywords: G15; G38; M41; M52; 330; corporate governance; accounting standards; financial reporting; comprehensive income; Polish and German markets